The importance of ports in the current global economy - Córdova, Miguel (2019)
Logistics is a central part of our every day’s life. We consume products and services that have been created in other countries and are delivered to us even from very far away at the lowest possible costs in the shortest time at the required quality. This note provides an insight into key areas of the global transportation network with ports being a crucial part connecting the waterside with the hinterland. It outlines major elements that need to be taken care of to maintain and enhance a smooth flow of goods and accompanying services able to fulfil our expectations.